A Porticus ad Nationes in Italica - Ojeda Nogales, David (Jahrbuch des Deutschen Archäologischen Instituts, 2023)
Five fragments of reliefs from Italica are deposited in several Spanish museums. They are all decorated with figures of nationes and belonged to a building that must have been built in the city in the Julio-Claudian period. Its model was the Porticus ad Nationes in Rome. The donators may have chosen that architectonic point of reference to demonstrate their adhesion to the principate of Augustus and to increase their possibilities of promotion in the capital of the Empire. Judging by the large number of senators from Italica in Rome, they achieved their objective.